사각형 해양구조물의 청수현상 발생과정에 대한 실험적 연구 - 채영준(Young Jun Chae); 이강남(Kang Nam Lee); 정광효(Kwang Hyo Jung); 서성부(Sung Bu Suh); 이재용(Jae Yong Lee) (Han-guk haeyang gonghak hoeji (Online), 2016)
An experimental study was performed to investigate the behavior of green water on a structure with a rectangular cross section under wave conditions, along with the flow characteristics in bubbly water flow. An experiment was conducted in a two-dimensional wave flume using an acrylic model (1/125) of FPSO BW Pioneer operating in the Gulf of Mexico under its design wave condition. The occurrence of green water, including its development, in front of the model was captured using a high-speed Charge Coupled Device (CCD) camera with the shadowgraph technique. Using consecutive images, the generation procedure for green water on the model was divided into five phases: flip through, air entrapment, wave run-up, wave overturning, and water shipping. In addition, the distinct water elevations of the green water were defined as the height of flip through, height of splashing jet, and height of freeboard exceedance, and showed a linear relationship with the incoming wave height.